INNOVATIVE PEDAGOGICAL TECHNOLOGIES IN THE MODERN SCHOOL - Khalikulov Erkin; Matyakubov Kamoliddin (Galaxy International Interdisciplinary Research Journal, 2022)
The article considers innovative activity in education as a socially significant practice aimed at the moral self-improvement of a person, which is able to ensure the transformation of all existing types of practices in society.